Localization of Epstein-Barr virus-encoded RNAs EBER-1 and EBER-2 in interphase and mitotic Burkitt lymphoma cells. - Schwemmle, M (1992)
The subcellular distribution of the small Epstein-Barr virus-encoded RNAs EBER-1 and EBER-2 has been investigated by using a high-resolution in situ hybridization technique. The distribution patterns in Raji cells of fluorescent oligodeoxynucleotides complementary to each RNA were detected by confocal laser scanning microscopy. Both RNAs were found in the cytoplasm as well as in the nuclei of interphase cells. In contrast, use of the same technique indicated an exclusively nuclear location for cellular U2 RNA. In the cytoplasm distribution of the EBERs was similar to that of the double-stranded RNA-dependent protein kinase, to which these RNAs can bind, and was coincident with the rough endoplasmic reticulum. In cells undergoing mitosis the EBERs became localized around the chromosomes, whereas the protein kinase remained uniformly distributed in the cytoplasm. A cytoplasmic location for EBER-1 and EBER-2 in interphase cells is consistent with the evidence for a role for these small RNAs in translational control.